Efek Washback Ujian Nasional Subyek Bahasa Inggris Pada Tingkat Sekolah Menengah Pertama (SMP) di Indonesia - M. Arif Rahman Hakim; Andri Saputra (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
A National Examination is commonly known as a standardised test held by a country, such as Indonesia, to gauge the students’ competence and the quality of their schools. Many people argue that the national examination implementation is likely to have positive and negative effects, not only on students but also on schools. This study aims to investigate the positive and negative effects of the National Examination of English subject in Indonesian junior high schools concerning English teachers’ classroom teaching and students’ learning. This study used a narrative literature review study, which reviews critiques and summarizes the literature body and draws conclusions regarding the topic question. By examining literature available and the authors’ experiences in doing the national examination as the participant and preparing students to face the examination, this paper showed that the National Examination of English emerges to have more negative impacts than positive ones. The result of this paper presents the authors’ recommendation to be used by key stakeholders in Indonesia that they should re-design the national examination to measure the students’ border competence effectively and objectively in English subject.